2011
DOI: 10.1681/asn.2010080881
|View full text |Cite
|
Sign up to set email alerts
|

CXCL16 Recruits Bone Marrow-Derived Fibroblast Precursors in Renal Fibrosis

Abstract: Although fibroblasts are responsible for the production and deposition of extracellular matrix in renal fibrosis, their origin is controversial. Circulating fibroblast precursors may contribute to the pathogenesis of renal fibrosis, but the signaling mechanisms underlying the recruitment of bone marrow-derived fibroblast precursors into the kidney in response to injury are incompletely understood. Here, in the unilateral ureteral obstruction model of renal fibrosis, tubular epithelial cells upregulated the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
186
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(191 citation statements)
references
References 40 publications
4
186
0
Order By: Relevance
“…Other embryonic sources were also proposed, for example from protein zero (P0) neural crest progenitors (166). A considerable number of studies have tackled the source of myofibroblasts during renal fibrosis (22,62,67,83,(172)(173)(174)(175)(176)(177)(178). In short, and in our opinion, the majority, if not all myofibroblasts arise from resident interstitial mesenchymal cells.…”
Section: The Role Of Interstitial Mesenchymal Cellsmentioning
confidence: 99%
“…Other embryonic sources were also proposed, for example from protein zero (P0) neural crest progenitors (166). A considerable number of studies have tackled the source of myofibroblasts during renal fibrosis (22,62,67,83,(172)(173)(174)(175)(176)(177)(178). In short, and in our opinion, the majority, if not all myofibroblasts arise from resident interstitial mesenchymal cells.…”
Section: The Role Of Interstitial Mesenchymal Cellsmentioning
confidence: 99%
“…We have recently provided unequivocal evidence that bone marrow-derived fibroblasts accumulate in the kidney in response to obstructive injury [9]. We demonstrate that CD45 and vimentin dual positive fibroblasts or CD11b and vimentin dual positive fibroblasts accumulate in the kidney in response to obstructive injury using confocal microscope.…”
Section: Introductionmentioning
confidence: 76%
“…Recent evidence indicates that they may originate from bone marrow-derived progenitor cells [5][6][7][8][9]. A study of mismatched kidney transplantation in humans has shown that the proportion of host-derived SMA-positive cells is approximately 30% in allografts undergoing chronic rejection compared with 10% in those without rejection [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was unexpected, as we have previously observed a critical role for CXCL16 in UUO and Ang‐II/uninephrectomy‐induced renal injury (Chen et al. 2011; Xia et al. 2013).…”
Section: Discussionmentioning
confidence: 99%